Стилістично знижена лексика в мові української преси початку ХХІ ст. - Панченко, Тетяна; Panchenko, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено тему вживання стилістично зниженої лексики зі зневажливим, лайливим та вульгарним відтінком у мові вітчизняної преси початку ХХІ століття. Проаналізовано розмовну лексику, яка є емоційно забарвленою та виконує функцію оцінки й характеристики. Зроблено висновки, що зневажливі, лайливі та вульгарні слова належать до розмовної лексики, яка є стилістично зниженою. У публіцистичних текстах вони часто вживані у статтях на суспільно-політичні теми, де описують вибори та учасників передвиборних перегонів, військові дії на Сході нашої держави і відносини України з Росією. The article considers the peculiarities of using stylistically reduced vocabulary, low unrefined lexics with derogatory, abusive and vulgar shade of meaning in the language of national press in the beginning of XXI century. The author draws on recent researches of linguists in the field of these words functioning and their role in modern Ukrainian literary language development. It was concluded that derogatory, abusive and vulgar words refer to spoken language which is emotive. In journalistic texts they are often used in articles on social and political issues, which describe the election and electoral contestants, military activities in the East of our country and Ukraine’s relations with Russia. Stylistically low unrefined lexics has negative-evaluative meaning, with these words the author expresses his own emotions and feelings of condemnation, contempt, disapproval, disgust to the events, that are taking place, or people who initiated those events. The author concludes that dismissive, abusive and vulgar language undermines linguistic-stylistic norms, but at the same time this lexics performs evaluative and expressive function as it is an ideal means of characterization of both people and events.
Stylistically Low Unrefined Lexics in the Language of Ukrainian Press in the Beginning of XXI Century
Keywords: публіцистичний стиль; стилістично знижена лексика; експресивність; негативно-оцінне значення; розмовні слова; journalistic style; stylistically reduced vocabulary; low unrefined lexics expressiveness; negative-evaluative meaning; colloquial words